Risky sexual behaviors and associated factors among adult patients on antiretroviral treatment at Mankweng Hospital in Limpopo Province, South Africa - Ntimana, Cairo B.; Mashaba, Reneilwe G.; Seakamela, Kagiso P.; Netshapapame, Tshifhiwa; Maimela, Eric (Frontiers in Public Health, 2023)
Background: Worldwide, it is estimated that 38 million people are HIV-positive and that over 36 million people have died from the virus Over 36 million people are estimated to have died from it, and 38 million are estimated to be HIV-positive worldwide. In South Africa, the prevalence of HIV was reported to be 20.6% with Limpopo Province having 17% HIV. Given the high rate of new HIV infection in Limpopo, there is therefore a need to assess factors promoting risky sexual behavior among people living with PLHIV in order to help design and develop behavioral interventions aimed at reducing risky behaviors among people living with PLHIV.Methods: This was a quantitative cross-sectional prospective study, conducted in Mankweng Hospital. The study consisted of 116 participants of which 40 were males and 76 were females aged 18 years and above. The participants were selected using purposive sampling. The data was analyzed using Statistical Package for Social Sciences version 27. A comparison of proportions was performed using Chi-Square. The association between risky sexual practice and sociodemographic factors was analyzed using multivariate logistic regression.The proportion of risky sexual practices in the total population was 48.3%. Participants who were Married participants, those participants aged 35-44, and those participants with tertiary qualifications were more likely to engage in risky sexual practices. Multivariate logistic regression showed widowed participants were less likely to practice risky sexual practices.The present study reported a high prevalence of risky sexual practices of 48.3%. Risky sexual behavior was determined by age, marital status, and the highest level of education. The proportion of married participants was higher in risky sexual behaviour. Based on the findings of the present study, it is recommended that targeted interventions and educational programs should be implemented to reduce risky sexual behavior among married individuals, individuals aged 35 to 44, and individuals with tertiary qualifications. The present study found no significant difference in sexual behaviour between participants who had no formal education, primary and secondary school.